2015
DOI: 10.1093/mutage/gev027
|View full text |Cite
|
Sign up to set email alerts
|

No oxidative stress or DNA damage in peripheral blood mononuclear cells after exposure to particles from urban street air in overweight elderly

Abstract: Exposure to traffic-related particulate matter (PM) has been associated with increased risk of lung disease, cancer and cardiovascular disease especially in elderly and overweight subjects. The proposed mechanisms involve intracellular production of reactive oxygen species (ROS), inflammation and oxidation-induced DNA damage studied mainly in young normal-weight subjects. We performed a controlled cross-over, randomised, single-blinded, repeated-measure study where 60 healthy subjects (25 males and 35 females)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Personal exposure to UFP, obtained by bicycling in streets with heavy traffic, was positively associated with levels of Fpg-sensitive sites in PBMCs, whereas there was no effect on levels of DNA strand breaks [49]. On the other hand, elderly and overweight subjects had unaltered levels of DNA strand breaks and Fpg-sensitive sites after exposure to urban street air in a controlled exposure study, whereas the total number of DNA lesions was positively associated with the particle number concentration [50]. Studies on high-dose exposure in animals have demonstrated mixed results for the association between pulmonary exposure to DEP and DNA strand breaks in lung tissue with certain studies showing increased levels of DNA damage [5153] and no effect [5456].…”
Section: Discussionmentioning
confidence: 99%
“…Personal exposure to UFP, obtained by bicycling in streets with heavy traffic, was positively associated with levels of Fpg-sensitive sites in PBMCs, whereas there was no effect on levels of DNA strand breaks [49]. On the other hand, elderly and overweight subjects had unaltered levels of DNA strand breaks and Fpg-sensitive sites after exposure to urban street air in a controlled exposure study, whereas the total number of DNA lesions was positively associated with the particle number concentration [50]. Studies on high-dose exposure in animals have demonstrated mixed results for the association between pulmonary exposure to DEP and DNA strand breaks in lung tissue with certain studies showing increased levels of DNA damage [5153] and no effect [5456].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of studies that have employed gradients in air pollution levels come from studies in Denmark where personal exposure to levels of ultrafine particles from traffic correlated with levels of Fpg-sensitive sites in PBMCs [66,67]. The same research group has reported that traffic-related air pollution in a chamber was associated with higher levels of DNA damage in PBMCs [68], whereas short-term exposure to even a high concentration of diesel exhaust (276 mg/m 3 for 3 h) had no effect on DNA strand breaks or oxidatively damaged DNA in PBMCs [69]. Wood smoke is another important source of particulate matter, which is increasingly relevant as an environmental exposure with the increasing number of wildfires.…”
Section: Environmental Exposurementioning
confidence: 99%
“…It has been reported that 8-oxo-2′-deoxyguanosine (8-OHdG) is a biomarker of DNA damage 88,94. 8-OHdG is one of several oxidative damage markers.…”
Section: Biomarkers Of Lung Diseases Caused By Particulate Mattermentioning
confidence: 99%
“…Transition metals generates excessive ROS, which significantly increases oxidative stress 95,96. Formatted 8-OHdG causes DNA damage and mediate the cytotoxicity and carcinogenicity 88. LINE-1, one of oxidative damage-related markers, has been suggested as a gene expression and DNA methylation markers 71,72,97.…”
Section: Biomarkers Of Lung Diseases Caused By Particulate Mattermentioning
confidence: 99%
See 1 more Smart Citation